THE RELATIONSHIP BETWEEN THE ACADEMIC ACHIEVEMENT OF PRIMARY SHOOL STUDENTS AND THE SCIENCE-MATHEMATICS ATTITUDES AND BASIC SKILL LEVELS - Barış ÇAYCI; Remzi KILIÇ (International Journal of Eurasia Social Sciences, 2017)
The place and effect of the basic skills and the attitudes developed towards the course or subject, especially in the primary school education, have an important place in the academic achievement of the students. The aim of this study is to determine the relation between the academic achievement of primary school students and the attitudes towards science and mathematics courses and the basic skill levels. Also to determine the relation of these relations to the demographic characteristics of the students’. The research is in the relational screening model. The universe of the research is composed of primary students in primary schools in Niğde province center. A total of 492 primary school 3rd and 4th grade students identified by cluster sampling from this universe. Data collection tools in the survey are; ‘Science Achievement Test’, ’Mathematics Achievement Test’ developed by the researchers, ’Basic Skill Scale’ developed by Padilla, Cronin and Twiest (1985), ’Mathematics Attitude Scale’ developed by Baykul (1999) and ’Science Attitude Scale’, developed by Nuhoğlu (2008). As a result of the research, it can be said that the success of the students in science and mathematics courses is influenced by the attitudes and basic skill levels.